Transfer of Millettia pachycarpa and M. entadoides to Derris (Fabaceae), supported by morphological and molecular data - Song, Zhuqiu; Pan, Bo (Phytotaxa, 2022)
Derris Lour. and Millettia Wight & Arn. are two genera of the tribe Millettieae (Fabaceae). The biggest difference between the two genera is that Derris has indehiscent, thin and winged pods, while Millettia has dehiscent, compressed and wingless pods, but some exceptions also exist. Because of their tardily dehiscent, inflated and wingless pods, two Asian liana species, Millettia pachycarpa Benth. and M. entadoides Z. Wei, were previously placed in Millettia sect. Macrospermae Dunn. However, their vegetative and floral characters, as well as the shape of seeds match with those of Derris very well. Phylogenetic analyses based on three chloroplast markers (trnK/matK, trnL-F IGS, and psbA-trnH IGS), and nuclear ITS/5.8S showed that the two species are nested within Derris, and separate from other samples of Millettia species with strong support. Therefore, the two species should be transferred from Millettia to Derris to maintain the monophyly of the latter, which inevitably results in an emendation of the generic circumscription of Derris. Due to the existence of Derris pachycarpa Merr., the second earliest valid epithet “taiwaniana” should be used for this taxon when transfering Millettia pachycarpa Benth. to Derris. Thus, a new combination, Derris taiwaniana (Hayata) Z.Q. Song, is proposed here. Millettia entadoides Z. Wei is recombined as Derris entadoides (Z. Wei) Z.Q. Song. The floral morphology of D. entadoides is described here for the first time, and it is reported as a new record from Thailand in this study.